EFFECT OF RESOURCE-SAVING MELON CULTIVATION METHODS ON YIELD - Ballasov Abdulhamid Ruzimahammad ugli; Yunusov Salohiddin Adhamovich (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract: This article presents the efficiency of cultivating 20-day-old melon seedlings under film in open fields. Planting 20-day-old seedlings under film produced higher marketable yields: 45.8 t/ha in the Obi Novvot variety, which is 20% higher than the control; 37.2 t/ha in the Samarkand Yellow variety, 16% higher than the control; and 35.8 t/ha in the Local Yellow variety, 15% higher than the control.